Emicizumab does not interfere with the activated clotting time. Issue 2 (21st January 2022) - Capdevila, Ladislas; Frère, Corinne; Desvages, Maximilien; Harroche, Annie; Bally, Cécile; Abbes, Ahmed; d'Oiron, Roseline; Frenzel, Laurent; Borgel, Delphine; Lasne, Dominique
Abstract: Introduction: The activated clotting time (ACT) is a useful marker of unfractionated heparin (UFH) activity during cardiopulmonary bypass (CPB) or cardiac catheterization. Emicizumab, recently approved for bleeding prevention in haemophilia A patients, acts like FVIII but does not need prior activation; it therefore shortens coagulation times in assays using intrinsic pathway activators and so is expected to shorten the ACT. Aim: To evaluated emicizumab's impact on heparin‐induced ACT (Hemochron®) prolongation. Methods: We measured the high‐range (HR) ACT in citrated blood samples from healthy donors (HDs) ( n  = 9), CPB patients ( n  = 3) and emicizumab‐treated patients ( n  = 5) after spiking with UFH and/or emicizumab. The low range (LR) ACT was also measured in spiked‐samples from HDs and emicizumab‐treated patients. Results: In HDs, the median [interquartile range] baseline HR‐ACTs were similar with and without emicizumab (129 [123–138] and 136 [115–141] s for 50 μg/ml, respectively); whatever the concentration of emicizumab (10 to 50 μg/ml), increasing the UFH concentration (1–5 UI/ml) prolonged the HR‐ACT. In blood from patients undergoing CPB, the HR‐ACT prolongation observed during this procedure was not masked by emicizumab at any concentration. Likewise, the addition of increasing concentrations of UFH to blood from emicizumab‐treated patients induced a concentration‐dependent prolongation of HR‐ACT. Baseline LR‐ACT were prolonged in emicizumab‐treated patients but as for HR‐ACT, emicizumab does not prevent heparin‐induced prolongation of LR‐ACT. Conclusion: Emicizumab does not interfere with UFH‐induced ACT prolongation. The hemochron® ACT can be used to monitor UFH in patients receiving emicizumab during CPB or cardiac catheterization.